Statistika z raziskovalnimi metodami - Rožman , Maja; Tominc, Polona (University of Maribor Press, 2024)
Statistics With Research Methods. In today’s rapidly changing business environment, the ability to understand and use statistics for making informed business decisions is crucial. The advancement of technology and the increasing size of data repositories enable detailed analysis and interpretation of data, which are essential for identifying key future trends and forming strategies based on these insights. In this collection, we discuss statistical methodological tools that assist in understanding the impact of various factors on specific economic and business categories and decisions. We analyze seasonal components in time series, define forecasting of values in future time units, analyze multidimensional variables, and approach statistical concepts of hypothesis testing regarding different properties of a statistical set based on a random sample. By understanding these processes, individuals can design effective strategies based on facts and data, prepare for future challenges, and leverage the dynamics of market changes.